Ian Watt and the figuration of the real (reading notes) - Vasconcelos, Sandra Guardini T. (Literatura e Sociedade, 2010)
This article aims to discuss the appropriation by Ian Watt ofsome crucial theoretical contributions from Critical Theory,which enabled the author of A ascensão do romance to incorporate to the tradition of Practical Criticism a concern with the sociohistorical processes which are formalised by the novelists he privileged in this work as a literary historian and critic. Here, Robinson Crusoe, the novel published by Daniel Defoe in 1719 is taken as a paradigmatic example.